Production of Al foams using the SDP method: Processing parameters and introduction a new sintering device - Cadena J.H.; Figueroa I.A.; Suarez M.A.; Novelo-Peralta O.; González G.; Lara-Rodríguez G.; Alfonso I. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The processing of aluminum (Al) foams with maximum porosity of around 70 %, regular pore size and interconnected pores were successfully produced by means of the powder metallurgy method of Sintering Dissolution Process (SDP). The metal powder used for the present study was Al powder with 99.5 % of purity and diameters between 75 μm and 200 μm. The chosen Space Holder Particles (SHP) were spherical carbamide CH4N2O particles with diameters ranging from 1 to 2 mm. The optimum sinterization temperature was found at 620°C, at this temperature, a number of necks between Al particles surfaces were observed; indicating a good cohesion between Al particles, while keeping the porous structure of the green compact. The level of porosity was dependent of the carbamide content and the voids formed within the Al particles after the sinterization process. The sample with 60 wt.% of carbamide showed the lowest yield stress value than those for the samples with 40 and 50 wt.%. The strain values significantly increased when the carbamide content increased from 40 to 60 wt.%. Finally, the results obtained from a new sintering device for producing metallic foams at temperatures below 900°C are also discussed.